The role of extension and financial services in boosting the effect of innovation investments for reducing poverty and hunger: A DEA approach - Nin-Pratt, Alejandro (Commission on Sustainable Agriculture Intensification, 2021)
Considering the new opportunities that ICT innovations bring to improve performance of financial and extension services, this study looks at the potential contribution of financial and extension services to the SDGs. The approach used extends the standard Data Envelopment Analysis (DEA) model to include longer-term management goals and find a solution that balances the efficient use of innovation investments and the achievement of policy goals, making this approach well suited for the analysis of the SDGs.